Penilaian Aset Kendaraan Bermotor pada Badan Pengelola Keuangan dan Aset Daerah (BPKAD) Kabupaten Belu - Aurelius Xaverian Wea; Cicilia A. Tungga; Rikhard T. Ch. Bolang (Universitas Kristen Indonesia Toraja, 2026)
This study aims to analyze the valuation of motor vehicle assets at the Regional Financial and Asset Management Agency (BPKAD) of Belu Regency. The background of the research is that there are still official vehicles in damaged or severely damaged condition that are still recorded as Regional Property (BMD), so an assessment is needed to obtain the limit value, liquidation value, and scrap value as the basis for asset elimination. The research uses a quantitative descriptive method with a case study approach on five motor vehicles owned by the Belu Regency Government, namely Honda Win in 2005, Honda Fit X in 2007, Suzuki Smash in 2007, Minibus in 2007, and Station Wagon in 2008. Data was collected through documentation, literature studies, and interviews. The assessment of vehicles that still have economic value is carried out using the market approach using the market data comparison method, while heavily damaged vehicles are assessed using the scrap value method. The results of the study show variations in market value and liquidation of vehicles that are still viable, as well as the value of scrap on heavily damaged vehicles. These findings confirm that the market approach can produce value estimates that reflect actual conditions, as well as become an objective basis for the elimination and transfer of motor vehicle assets owned by local governments.